An uracil-linked hydroxyflavone probe for the recognition of ATP - Bojtár, Márton; Janzsó-Berend, Péter Zoltán; Mester, Dávid; Hessz, Dóra; Kállay, Mihály; Kubinyi, Miklós; Bitter, István (Beilstein Journal of Organic Chemistry, 2018)
Background: Nucleotides are essential molecules in living systems due to their paramount importance in various physiological processes. In the past years, numerous attempts were made to selectively recognize and detect these analytes, especially ATP using small-molecule fluorescent chemosensors. Despite the various solutions, the selective detection of ATP is still challenging due to the structural similarity of various nucleotides. In this paper, we report the conjugation of a uracil nucleobase to the known 4’-dimethylamino-hydroxyflavone fluorophore.Results: The complexation of this scaffold with ATP is already known. The complex is held together by stacking and electrostatic interactions. To achieve multi-point recognition, we designed the uracil-appended version of this probe to include complementary base-pairing interactions. The theoretical calculations revealed the availability of multiple complex structures. The synthesis was performed using click chemistry and the nucleotide recognition properties of the probe were evaluated using fluorescence spectroscopy.Conclusions: The first, uracil-containing fluorescent ATP probe based on a hydroxyflavone fluorophore was synthesized and evaluated. A selective complexation with ATP was observed and a ratiometric response in the excitation spectrum.
Keywords: ATP sensing; base-pairing; fluorescent probes; 3-hydroxyflavone; nucleotide recognition

(untitled) - Knowles, J. R. (Annu. Rev. Biochem., 1980)

Molecular Biology of the Cell - Alberts, B.; Johnson, A.; Lewis, J.; Raff, M.; Roberts, K.; Walter, P. (Garland Science, 2002)

(untitled) - Gourine, A. V.; Llaudet, E.; Dale, N.; Spyer, K. M. (Nature, 2005)

(untitled) - Higgins, C. F.; Hiles, I. D.; Salmond, G. P. C.; Gill, D. R.; Downie, J. A.; Evans, I. J.; Holland, I. B.; Gray, L.; Buckel, S. D.; Bell, A. W.; Hermodson, M. A. (Nature, 1986)

(untitled) - Hargrove, A. E.; Nieto, S.; Zhang, T.; Sessler, J. L.; Anslyn, E. V. (Chem. Rev., 2011)

(untitled) - Kim, S. K.; Lee, D. H.; Hong, J.-I.; Yoon, J. (Acc. Chem. Res., 2009)

(untitled) - Duke, R. M.; Veale, E. B.; Pfeffer, F. M.; Kruger, P. E.; Gunnlaugsson, T. (Chem. Soc. Rev., 2010)

(untitled) - Lee, S.; Yuen, K. K. Y.; Jolliffe, K. A.; Yoon, J. (Chem. Soc. Rev., 2015)

(untitled) - Dong, J.; Zhao, M. (TrAC, Trends Anal. Chem., 2016)

(untitled) - Neelakandan, P. P.; Hariharan, M.; Ramaiah, D. (Org. Lett., 2005)

(untitled) - Neelakandan, P. P.; Hariharan, M.; Ramaiah, D. (J. Am. Chem. Soc., 2006)

(untitled) - Ramaiah, D.; Neelakandan, P. P.; Nair, A. K.; Avirah, R. R. (Chem. Soc. Rev., 2010)

(untitled) - Liu, X.; Ngo, H. T.; Ge, Z.; Butler, S. J.; Jolliffe, K. A. (Chem. Sci., 2013)

(untitled) - Liu, X.; Smith, D. G.; Jolliffe, K. A. (Chem. Commun., 2016)

(untitled) - Bojtár, M.; Kozma, J.; Szakács, Z.; Hessz, D.; Kubinyi, M.; Bitter, I. (Sens. Actuators, B, 2017)

(untitled) - Xu, Z.; Singh, N. J.; Lim, J.; Pan, J.; Kim, H. N.; Park, S.; Kim, K. S.; Yoon, J. (J. Am. Chem. Soc., 2009)

(untitled) - Wang, D.; Zhang, X.; He, C.; Duan, C. (Org. Biomol. Chem., 2010)

(untitled) - Kim, H. N.; Moon, J. H.; Kim, S. K.; Kwon, J. Y.; Jang, Y. J.; Lee, J. Y.; Yoon, J. (J. Org. Chem., 2011)

(untitled) - Czirok, J. B.; Bojtár, M.; Hessz, D.; Baranyai, P.; Drahos, L.; Kubinyi, M.; Bitter, I. (Sens. Actuators, B, 2013)

(untitled) - Li, X.; Guo, X.; Cao, L.; Xun, Z.; Wang, S.; Li, S.; Li, Y.; Yang, G. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ojida, A.; Takashima, I.; Kohira, T.; Nonaka, H.; Hamachi, I. (J. Am. Chem. Soc., 2008)

(untitled) - Sakamoto, T.; Ojida, A.; Hamachi, I. (Chem. Commun., 2009)

(untitled) - Moro, A. J.; Cywinski, P. J.; Körsten, S.; Mohr, G. J. (Chem. Commun., 2010)

(untitled) - Kurishita, Y.; Kohira, T.; Ojida, A.; Hamachi, I. (J. Am. Chem. Soc., 2010)

(untitled) - Weitz, E. A.; Chang, J. Y.; Rosenfield, A. H.; Pierre, V. C. (J. Am. Chem. Soc., 2012)

(untitled) - Chao, D.; Ni, S. (Sci. Rep., 2016)

(untitled) - Kumari, N.; Zelder, F. (Chem. Commun., 2015)

(untitled) - Tang, J.-L.; Li, C.-Y.; Li, Y.-F.; Zou, C.-X. (Chem. Commun., 2014)

(untitled) - Wang, L.; Yuan, L.; Zeng, X.; Peng, J.; Ni, Y.; Er, J. C.; Xu, W.; Agrawalla, B. K.; Su, D.; Kim, B.; Chang, Y.-T. (Angew. Chem., Int. Ed., 2016)

(untitled) - Maity, D.; Li, M.; Ehlers, M.; Schmuck, C. (Chem. Commun., 2017)

(untitled) - You, L.; Zha, D.; Anslyn, E. V. (Chem. Rev., 2015)

(untitled) - Langton, M. J.; Serpell, C. J.; Beer, P. D. (Angew. Chem., Int. Ed., 2016)

(untitled) - Xu, Z.; Kim, S. K.; Yoon, J. (Chem. Soc. Rev., 2010)

(untitled) - Yushchenko, D. A.; Vadzyuk, O. B.; Kosterin, S. O.; Duportail, G.; Mély, Y.; Pivovarenko, V. G. (Anal. Biochem., 2007)

(untitled) - Sengupta, P. K.; Kasha, M. (Chem. Phys. Lett., 1979)

(untitled) - Klymchenko, A. S.; Demchenko, A. P. (J. Am. Chem. Soc., 2002)

(untitled) - Klymchenko, A. S.; Demchenko, A. P. (Phys. Chem. Chem. Phys., 2003)

(untitled) - Demchenko, A. P. (FEBS Lett., 2006)

(untitled) - Yushchenko, D. A.; Fauerbach, J. A.; Thirunavukkuarasu, S.; Jares-Erijman, E. A.; Jovin, T. M. (J. Am. Chem. Soc., 2010)

(untitled) - Strizhak, A. V.; Postupalenko, V. Y.; Shvadchak, V. V.; Morellet, N.; Guittet, E.; Pivovarenko, V. G.; Klymchenko, A. S.; Mély, Y. (Bioconjugate Chem., 2012)

(untitled) - Zamotaiev, O. M.; Postupalenko, V. Y.; Shvadchak, V. V.; Pivovarenko, V. G.; Klymchenko, A. S.; Mély, Y. (Bioconjugate Chem., 2011)

(untitled) - Chen, S.; Hou, P.; Zhou, B.; Song, X.; Wu, J.; Zhang, H.; Foley, J. W. (RSC Adv., 2013)

(untitled) - Shvadchak, V. V.; Klymchenko, A. S.; de Rocquigny, H.; Mély, Y. (Nucleic Acids Res., 2009)

(untitled) - Pivovarenko, V. G.; Vadzyuk, O. B.; Kosterin, S. O. (J. Fluoresc., 2006)

(untitled) - Pivovarenko, V. G.; Bugera, O.; Humbert, N.; Klymchenko, A. S.; Mély, Y. (Chem. – Eur. J., 2017)

(untitled) - Yakovchuk, P.; Protozanova, E.; Frank-Kamenetskii, M. D. (Nucleic Acids Res., 2006)

(untitled) - Halgren, T. A. (J. Comput. Chem., 1999)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1997)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Hehre, W. J.; Ditchfield, R.; Pople, J. A. (J. Chem. Phys., 1972)

(untitled) - Miertuš, S.; Scrocco, E.; Tomasi, J. (Chem. Phys., 1981)

Marvin 6.1.0 (ChemAxon, 2013)

(untitled) - Neese, F. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2012)

(untitled) - Nagy, P. R.; Kállay, M. (J. Chem. Phys., 2017)

(untitled) - Kendall, R. A.; Dunning, T. H., Jr; Harrison, R. J. (J. Chem. Phys., 1992)

(untitled) - Nguyen, K.; Fazio, M.; Kubota, M.; Nainar, S.; Feng, C.; Li, X.; Atwood, S. X.; Bredy, T. W.; Spitale, R. C. (J. Am. Chem. Soc., 2017)

(untitled) - Smith, M. A.; Neumann, R. M.; Webb, R. A. (J. Heterocycl. Chem., 1968)

(untitled) - Anand, N.; Singh, P.; Sharma, A.; Tiwari, S.; Singh, V.; Singh, D. K.; Srivastava, K. K.; Singh, B. N.; Tripathi, R. P. (Bioorg. Med. Chem., 2012)

(untitled) - Lee, M. H.; Kim, J. S.; Sessler, J. L. (Chem. Soc. Rev., 2015)

(untitled) - Giner-Sorolla, A.; Medrek, L. (J. Med. Chem., 1966)

(untitled) - Chan, T. R.; Hilgraf, R.; Sharpless, K. B.; Fokin, V. V. (Org. Lett., 2004)

(untitled) - Thordarson, P. (Chem. Soc. Rev., 2011)

(untitled) - Brynn Hibbert, D.; Thordarson, P. (Chem. Commun., 2016)